THE RELATIONSHIP OF PHYSICAL ACTIVITY, BMI, AND OSTEOPOROSIS RISK IN POSTAMENOPAUSE WOMEN IN NUSAWANGKAL VILLAGE, CILACAP REGENCY IN 2020 - Galih Riskian; Anies Setiowati (Nusa Cendana University, 2022)
Osteoporosis is a degenerative disease. Recent research from the International Osteoporosis Foundation (IOF) revealed that 1 in 4 women in Indonesia with an age range of 50-80 years have a risk of developing osteoporosis. The purpose of this study was to find out if there is a relationship of physical activity with the risk of osteoporosis in postmenopausal women in Nusawangkal Village of Cilacap Regency in 2020.This type of research is non-experimental quantitative research, using cross sectional design approaches. With a population of 3122 Nusawangkal village communities sampling using Purposive Sampling technique which is a sample determination technique with certain considerations. The sample was taken using a purposive sampling technique of 25 people. The data is retrieved using questionnaires that have been shared with respondents. The data analysis used in this study is descriptive data analysis (Unvariate Analysis) which aims to explain the characteristics of each research variable. Chi square test results have an Asymp value. Sig is 0.016 (< 0.05). In accordance with the basis of chi square test decision making, it can be concluded that there is a significant relationship between body mass index and the risk of osteoporosis in postmenopausal women. The conclusion of this study there is a significant relationship between body mass index and the risk of osteoporosis in postmenopausal women in Nusawangkal Village, Cilacap Regency.